2022
DOI: 10.3389/fcvm.2022.993112
|View full text |Cite
|
Sign up to set email alerts
|

Components of a healthy diet and different types of physical activity and risk of atherothrombotic ischemic stroke: A prospective cohort study

Abstract: BackgroundDiet and physical activity (PA) are modifiable risk factors thought to influence the risk of ischemic stroke (IS). However, few studies have examined their effect on different subtypes of IS.AimTo examine components of overall diet quality and different types of PA in relation to the risk of atherothrombotic IS (aIS).Materials and methodsThe study population included 23,797 participants (mean age 58 years; 63% women) from the Malmö Diet and Cancer Study cohort. Participants were enrolled between 1991… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the importance of the dietary risk factor, including SFA, in the occurrence of ischemic stroke was discussed according to the etiology of stroke (39), adherence to the Mediterranean diet rich in nuts, olive oil, fruits and vegetables, low SFA, dairy products, and red meat is associated with a decreased risk in stroke (26).…”
Section: Discussion Main Resultsmentioning
confidence: 99%
“…The link between SFA and stroke is the most debated ( 40 ). Previous studies have demonstrated an association between SFA and stroke ( 41 ) but also the opposite ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven studies were included in the analyses of beverage consumption and CVD risk. A total of 207,460 cases of hypertension (n = 10), 23,757 cases of CHD (n = 8), and 15,830 cases due to stroke (n = 9) in 1,395,468 participants were included in the present study (32,33,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Compared with participants in the bottom category of SSBs, those in the top category had a 12% higher risk of hypertension (RR: 1.12; 95% CI: 1.08, 1.17; P heterogeneity = 0.05; I 2 = 50.3%; n = 8; Figure 2; Supplementary Figure 4).…”
Section: Association Between Beverages and Cvdmentioning
confidence: 99%